2013
DOI: 10.1111/bcp.12121
|View full text |Cite
|
Sign up to set email alerts
|

A time‐to‐event model for acute rejections in paediatric renal transplant recipients treated with ciclosporin A

Abstract: AIMSCiclosporin A (CsA) dosing in immunosuppression after paediatric kidney transplantation remains challenging, and appropriate target CsA exposures (AUCs) are controversial. This study aimed to develop a time-to-first-acute rejection (AR) model and to explore predictive factors for therapy outcome. METHODSPatient records at the Children's Hospital in Helsinki, Finland, were analysed. A parametric survival model in NONMEM was used to describe the time to first AR. The influences of AUC and other covariates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A few studies used survival models with time–dependent covariates to investigate the relationships between AR and longitudinal exposure to a single immunosuppressive drug (i.e., joint model for MPA, 33 Belatacept, 34 CsA, 7 and Cox model for tacrolimus 35 ). Within the observed concentration ranges, CsA 7 as well as Belatacept 34 longitudinal exposures were not statistically significant predictors of the hazard of AR. For tacrolimus, the association of time–varying tacrolimus trough levels with AR occurring in the first 6 months posttransplantation was analyzed using a Cox model 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies used survival models with time–dependent covariates to investigate the relationships between AR and longitudinal exposure to a single immunosuppressive drug (i.e., joint model for MPA, 33 Belatacept, 34 CsA, 7 and Cox model for tacrolimus 35 ). Within the observed concentration ranges, CsA 7 as well as Belatacept 34 longitudinal exposures were not statistically significant predictors of the hazard of AR. For tacrolimus, the association of time–varying tacrolimus trough levels with AR occurring in the first 6 months posttransplantation was analyzed using a Cox model 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies challenge the benefit of TDM for CNIs based on the recommended targets. The studies minimizing exposure to CNIs (i.e., Symphony 5 and Caesar for CsA 6 ) found a low impact of minimization of CNI exposure on AR risk, whereas modeling studies found contradictory results 7 , 8 . The added value of TDM for MPA is still under debate 9 .…”
mentioning
confidence: 99%
“…We would especially like to thank Mats O. Karlsson, Kajsa Harling, Anne-Gaëlle Dosne, Anders Kristoffersson, Oskar Alskär and Giulia Corn for discussions and extensive testing. In addition, we would like to thank the authors of (11)(12)(13)(14) who gave us permission to use their NONMEM model files and data sets for the numerical experiments.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The probability of not having an event (i.e., no dropout) by time t is described by the survivor function S ( t ), which is determined by the hazard. A flexible empirical function was applied as described in Frobel et al [ 14 ], where the hazard changes in a step-wise fashion at given breakpoints. To avoid discontinuities in the hazard when passing a breakpoint, often leading to numerical problems during estimation, several sigmoidal functions were connected to achieve some smoothness.…”
Section: Methodsmentioning
confidence: 99%